The role of previously unmeasured organic acids in the pathogenesis of severe malaria - Herdman, M. Trent (2017)
Introduction: Severe falciparum malaria is commonly complicated by metabolic acidosis. Together with lactic acid (LA), other previously unmeasured acids have been implicated in the pathogenesis of falciparum malaria. Methods: In this prospective study, we characterised organic acids in adults with severe falciparum malaria in India and Bangladesh. Liquid chromatography-mass spectrometry was used to measure organic acids in plasma and urine. Patients were followed until recovery or death. Results: Patients with severe malaria (n=138), uncomplicated malaria (n=102), sepsis (n=32) and febrile encephalopathy (n=35) were included. Strong ion gap (mean±SD) was elevated in severe malaria (8.2 mEq/L±4.5) and severe sepsis (8.6 mEq/L±7.7) compared with uncomplicated malaria (6.0 mEq/L±5.1) and encephalopathy (6.6 mEq/L±4.7). Compared with uncomplicated malaria, severe malaria was characterised by elevated plasma LA, hydroxyphenyllactic acid (HPLA), α-hydroxybutyric acid and β-hydroxybutyric acid (all P<0.05). In urine, concentrations of methylmalonic, ethylmalonic and α-ketoglutaric acids were also elevated. Multivariate logistic regression showed that plasma HPLA was a strong independent predictor of death (odds ratio [OR] 3.5, 95 % confidence interval [CI] 1.6–7.5, P=0.001), comparable to LA (OR 3.5, 95 % CI 1.5–7.8, P=0.003) (combined area under the receiver operating characteristic curve 0.81). Conclusions: Newly identified acids, in addition to LA, are elevated in patients with severe malaria and are highly predictive of fatal outcome. Further characterisation of their sources and metabolic pathways is now needed.